"From dawn to twilight" communication in the formation of grandparent and grandchild relations - Manuel, Marie Charlene Anne B.
The main thrust of this study was to understand the role of interpersonal communication in determining the kind of relationship that form or exist between grandparents and grandchildren. Its general objective was to determine the communication patterns between grandparents and grandchildren. This included finding out the roles grandparents hold within the family network, role expectations as a grandchild and as a grandparent, the benefits each derive from the relationship and various modes of communication engaged in. As in any relationship, there are factors that cause interaction to vary, which thus affect the type of relationship formed. Grandparent-grandchild relationships are not an exception. In this study, age, geographical proximity, and health vitality of both the grandparent and grandchild were characteristics considered, to see as to the extent these factors affect interaction. To pursue the objectives of this study, the researcher conducted in-depth interviews with four grandparent-grandchild dyads, each having different characteristics (age, geographic proximity, and health vitality). These characteristics were treated as independent variables. The dependent variables, on the other hand, the interpersonal communication/interaction between the grandparents and grandchildren, and the style of grand-parenting used. In the analysis of the data, the researcher followed the phenomenological stance by deriving content from the symbols and meanings the respondents attributed to their experiences. The findings of the study revealed that certain characteristics affect the interpersonal communication between grandparents and grandchildren, i.e., the ages of the grandparent and grandchild, their state of health (particularly, the health of grandparents) and the kind of relationship the grandchild had with her family (especially the mother). Surprisingly, contrary to previous studies done in the west, distance or geographical proximity did not appear to be important factors in determining the kind of relationship grandparents and grandchildren had with each other. This may be attributed to the mores and norms Filipinos have towards the elderly, that they must be respected and cared for. The findings further revealed that the more frequent interaction occurred, and the more significant these were, the closer grandparents and grandchildren are to each other. The dyads that had low frequency of interaction and little depth and breadth in their verbal interactions were those who were not very close. The revelations of the study verify the fact that when the existence of communication is indeed an indication of a relationship, it is the frequency, content and novelty of the verbal and non-verbal communication that dictates what kind of relationship persists.